The Effectiveness of Investigation of Narcotics Crimes with the Role of Informants to Realize Harkamtibmas in Bandar Lampung Police Jurisdiction - Sulthan Ali (Advances in Police Science Research Journal, 2022)
This research is motivated by the increasing number of narcotics crimes both nationally and in Lampung Province, but at the Bandar Lampung Police, it is known that there is no increase in the disclosure of narcotics crimes. The purpose of this research is to reveal whether investigations with the role of informants have been effective and how investigations carried out with the role of informants are effective in realizing Harkamtibmas. This research was conducted with a qualitative approach, using phenomenological methods. The focus of the research is on the performance of the investigation which is compared with the implementation of Patrol activities and Bhabinkamtimbas activities as a measure of the maintenance of Kamtibmas. Data collection techniques were carried out by interviews, observations, documents, questionnaires and, Focused Group Discussions. The validity of the data was checked using triangulation of methods and sources, with the Miles-Huberman model data analysis technique. The results of the study stated that the investigation with the role of the informant was not yet fully effective, this happened due to the lack of infrastructure needed for investigation (office tools, stationery), the absence of supporting technology (tapping tools, trackers, direct finder, data recover, surveillance camera) , the implementation of the provisions following the Technical Guidelines, the quality of personnel is not ideal yet. However, the role of informants can realize Harkamtibmas by facilitating investigations, accelerating investigations, minimizing costs and risks to assisting in carrying out investigations. Based on the results of the study, the authors suggest to unite the sub-unit of investigators, add additional tools/technology to support investigations, increase personnel capabilities, improve the Narcotics networking and implement Narcotics socialization. If possible, the organization can be developed into three units, to increase investigative capabilities that will increase organizational effectiveness.